2017
DOI: 10.1111/auar.12169
|View full text |Cite
|
Sign up to set email alerts
|

Does the Presence of Female Executives Curb Earnings Management? Evidence from Korea

Abstract: We investigate the role of female executives in curbing earnings management behaviour in Korea, a country known for its strong male-dominant culture. In a sample of Korean firms from 2002 to 2010, we find that female presence in top management is negatively associated with discretionary accruals, suggesting that gender diversity in senior management deters opportunistic financial reporting even in a highly male-dominant corporate environment. Further, this association is primarily observed in firms with strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
3
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 44 publications
1
20
3
4
Order By: Relevance
“…The results of this study are supported by research conducted by Ye et al (2010), who also found that the gender of the management board did not affect corporate earnings management. The results of this study contradict the research conducted by Kim et al (2017), Hala (2019), Harakeh et al (2019), who found that females in the management board negatively affected earnings management.…”
Section: Female In the Board Of Directors And Earnings Managementcontrasting
confidence: 99%
See 2 more Smart Citations
“…The results of this study are supported by research conducted by Ye et al (2010), who also found that the gender of the management board did not affect corporate earnings management. The results of this study contradict the research conducted by Kim et al (2017), Hala (2019), Harakeh et al (2019), who found that females in the management board negatively affected earnings management.…”
Section: Female In the Board Of Directors And Earnings Managementcontrasting
confidence: 99%
“…Previous studies relating to the influence of gender of the board of directors on earnings management conducted by Hala (2019) found that women in upper management had a negative effect on earnings management. This is also supported by research conducted by Harakeh et al (2019) and Kim et al (2017). The opposite is obtained from research conducted by Ye et al (2010) found that there is no difference in earnings quality in firms managed by men and women.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Potential gender differences at the executive level have also been examined in the financial reporting context. Gender differences in the top management team and opportunistic financial reporting have been found by Kim et al (2017). Zalata et al .…”
Section: Literature Review and Hypothesesmentioning
confidence: 75%
“…Potential gender differences at the executive level have also been examined in the financial reporting context. Gender differences in the top management team and opportunistic financial reporting have been found by Kim et al (2017). Zalata et al (2019) report observable differences in financial reporting behaviour between male and female CEOs and attribute the difference to risk aversion rather than ethical sensitivity.…”
mentioning
confidence: 92%